Gray Matter Volume of Thalamic Nuclei in Traumatized North Korean Refugees - Lee, Jiye; Kim, Nambeom; Jeong, Hyunwoo; Jun, Jin Yong; Yoo, So Young; Lee, So Hee; Lee, Jooyoung; Lee, Yu Jin; Kim, Seog Ju (Frontiers in Psychiatry, 2022)
The current study investigated differences in the regional gray matter (GM) volume of specific thalamic nuclei between North Korean (NK) refugees and South Korean (SK) residents. It also investigated associations between thalamic GM volume changes and psychological symptoms. Psychological evaluations and magnetic resonance imaging were conducted on 50 traumatized NK refugees and 55 non-traumatized SK residents. The regional GM volume ratios in the bilateral thalami were calculated for all participants using voxel-based morphometry. NK refugees showed greater GM volume ratios in the right pulvinar and left anterior nuclei compared with SK residents. NK refugees also exhibited more depressive symptoms than SK residents. However, increased GM volume ratios in both right pulvinar and left anterior nuclei were correlated with fewer depressive symptoms in NK refugees, but not in SK residents. The findings indicate that traumatized NK refugees had increased GM volumes in the right pulvinar and left anterior nuclei, which were associated with fewer depressive symptoms. The enlarged specific thalamic nuclei presented among refugees in the current study might be associated with a neurobiological compensatory mechanism that prevents the development or progression of depression in refugees after repetitive traumatic experiences.